PENERAPAN METODE DESAIN SPRINT PADA SISTEM PENDISTRIBUSIAN DAN PENGADAAN BARANG MENGGUNAKAN MOBILE - Adhie Thyo Priandika; Wahyu Widiantoro (Universitas Teknokrat Indonesia, 2021)
CV Ra'Abas Bandarlampung is a trading business engaged in the distribution and procurement of goods that distributes its merchandise to customers. Problems that exist in the distribution process, namely the manufacture of sales notes and invoices for delivery still done manually, namely by writing on notes and invoices for delivery of goods to be given to customers so that it slows down employee performance. The sprint method is a method for building product concepts and prototypes within 5 minutes. a day where it has 5 very communicative and interactive stages to bring out all ideas, inspiration, creativity, existing problems.. The next stage is to make a sketch of the application to be built, the sketch made is a sketch for the login display, dashboard, customer data, goods data, supplier data, procurement data, receipt data, and goods distribution data. The next stage is to make a decision from the previous stage by determining the results of the sketch that has been made from the procurement and distribution system of goods that can overcome the problems that occur in CV Ra'Abas.